2019
DOI: 10.1016/j.adaj.2018.10.022
|View full text |Cite|
|
Sign up to set email alerts
|

Feasibility and acceptance of oral human papillomavirus detection in the dental office

Abstract: Background. Oral human papillomavirus (HPV) infection is the principal underlying cause of a dramatic rise in oropharyngeal cancer. Dentistry can play an important role in developing clinical algorithms for secondary prevention. Methods. This cross-sectional pilot study was conducted with practices of the National Dental Practice-Based Research Network. It evaluated the feasibility and acceptability of screening and testing procedures as judged by practitioners and patients. Tablets were used for patient scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…This environment may enable healthcare professions to ask about individual risk factors and ultimately to look more closely for oral lesions, which may indicate OPCa. Our findings add to the evidence that dentists and dental hygienists are well positioned to develop protocols for oral HPV detection and that such procedures are feasible and acceptable to both dental healthcare providers and patients (24).…”
Section: Discussion Discussion Of Findingssupporting
confidence: 54%
See 2 more Smart Citations
“…This environment may enable healthcare professions to ask about individual risk factors and ultimately to look more closely for oral lesions, which may indicate OPCa. Our findings add to the evidence that dentists and dental hygienists are well positioned to develop protocols for oral HPV detection and that such procedures are feasible and acceptable to both dental healthcare providers and patients (24).…”
Section: Discussion Discussion Of Findingssupporting
confidence: 54%
“…Whitehead et al (22) found that being closeted to healthcare providers may lead to lower rates of healthcare use among GBM, and Facione and Facione (23) demonstrated that prejudice against LGBTQ people is associated with reduced rates of cancer screening. However, Rindal et al (24) demonstrated that among a group of 36 dental healthcare providers, 90% reported being highly comfortable with asking patients about sexual behaviors during oral HPV screening, and 69% of patients surveyed (N = 1,025) reported being comfortable if asked about them. Perhaps the findings in Rindal et al (24) indicate that conversations about sexual activity are becoming more commonplace in dentistry.…”
Section: Discussion Discussion Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three subjects with persistent HPV-16 infection >30 mo were evaluated by an otolaryngologist, leading to the identification of HPV-positive oropharynx cancer in 1 subject ( Tang et al 2020 ). The feasibility of performing a risk-based opportunistic screening for oral HPV infection in dental offices has been tested ( Rindal et al 2019 ). In this study, subjects presenting for routine dental evaluation took a short screening questionnaire to assess risk for prevalent oral HPV infection.…”
Section: Screening For Hpv-positive Oropharyngeal Cancermentioning
confidence: 99%
“…When recruiting/ enrolling on a national scale, it can be challenging to stop enrollment at a specific date, especially when simultaneously wanting to maintain optimal relationships with practitioners who have devoted significant effort to a specific study. Three studies were excluded: (1) Suspicious Occlusal Caries study because patients were not followed [24]; (2) Anterior Open bite study because only patients whose treatment was considered ended or completed, viz., open-bite closed, were requested to return in 18 months [25]; and (3) Risk for Oral Cancer study because only patients with a positive high-risk human papillomavirus test (N = 11) result were requested to come in for a 6-month visit [26]. Two out of the five studies described below required in-person FU visits.…”
Section: Methodsmentioning
confidence: 99%